An investigation into the effects of resonances on the time delay estimate for leak detection in buried plastic water distribution pipes - Almeida, Fabricio C. L. [UNESP]; Brennan, Michael J. [UNESP]; Joseph, Phillip F.; Dray, Simon; Witfield, Stuart; Paschoalini, Amarildo T. [UNESP]; Cunha, A.; Caetano, E.; Ribeiro, P.; Muller, G. (European Assoc Structural Dynamics, 2014)
In water distribution systems, old metallic pipes have been replaced by plastic pipes due to their deterioration over time. Although acoustic methods are effective in finding leaks in metallic pipes, they have been found to be problematic when applied to plastic pipes due to the high damping within the pipe wall and the surrounding medium. This is responsible for the leak signal not traveling long distances. Moreover, the leak energy in plastic pipes is generally located at a narrow frequency range located at low frequencies. However, the presence of resonances can narrow even more this frequency range. In order to minimise the influence of background noise and resonances on the calculation of the time delay estimate, band-pass filters are often used to supress undesirable frequency components of the noise. The objective of this paper is to investigate the influence of resonances in the pipe system (pipe, valves, connections and hydrants), on the time delay estimate calculated using acoustic signals. Analytical models and actual leak data collected in a bespoke rig located in the United Kingdom are used to investigate this feature.
Keywords: Leak detection; Plastic pipes; Resonances